The control of metabolic traits by octopamine and tyramine in invertebrates. - Roeder, T. (Journal of Experimental Biology, 2020)
Octopamine (OA) and tyramine (TA) are closely related biogenic monoamines that act as signalling compounds in invertebrates, where they fulfil the roles played by adrenaline and noradrenaline in vertebrates. Just like adrenaline and noradrenaline, OA and TA are extremely pleiotropic substances that regulate a wide variety of processes, including metabolic pathways. However, the role of OA and TA in metabolism has been largely neglected. The principal aim of this Review is to discuss the roles of OA and TA in the control of metabolic processes in invertebrate species. OA and TA regulate essential aspects of invertebrate energy homeostasis by having substantial effects on both energy uptake and energy expenditure. These two monoamines regulate several different factors, such as metabolic rate, physical activity, feeding rate or food choice that have a considerable influence on effective energy intake and all the principal contributors to energy consumption. Thereby, OA and TA regulate both metabolic rate and physical activity. These effects should not be seen as isolated actions of these neuroactive compounds but as part of a comprehensive regulatory system that allows the organism to switch from one physiological state to another.